Cultural Dimensions in Occupational Safety in Aceh - Suryaningrum, Melati (Omnia Tempus, 2025)
qualitative methodology grounded in an extensive literature review. While occupational safety is often approached through technical and regulatory frameworks, this research argues for a culturally embedded understanding that accounts for local socio-religious values, power dynamics, and communal norms. The study utilizes Hofstede’s cultural dimensions as a theoretical lens to interpret how variables such as power distance, collectivism, and uncertainty avoidance shape workplace safety behaviors, perceptions, and policy compliance in Acehnese industrial settings. Data were synthesized from academic literature, policy documents, and regional studies published between 2000 and 2024, with thematic content analysis employed to extract recurring patterns and conceptual linkages. The findings reveal that power distance inhibits hazard reporting, collectivist values shape group accountability, religious doctrines both motivate and constrain safety behavior, and institutional gaps hinder the alignment of national safety policies with local cultural realities. The study further highlights the need for culturally responsive and participatory safety interventions that integrate Islamic values, community leadership, and localized governance. Theoretically, this research challenges universalist assumptions in safety discourse by emphasizing cultural specificity and advocating for a more nuanced, context-sensitive approach. Practically, it urges policymakers and managers to embed moral legitimacy and communal engagement in occupational safety frameworks. The study concludes that sustainable improvements in workplace safety in Aceh require a paradigm shift from technical compliance to cultural integration, offering insights that are relevant to similarly complex and multicultural settings globally.